Определение скорости пылегазовой смеси в рабочей зоне мельницы ударно-отражательного действия - Лещенко, Е. В.; Сорока, П. И.; Кравец, В. И.; Кравец, А. В.; Опарин, С. А. (НТУ "ХПИ", 2007)
В статті запропоновано метод визначення швидкості пилогазової суміші в робочій зоні млина ударно-відбівної дії на основі потужності, яка витрачається млином на подолання опору бил потоку пилогазової суміші. Встановлено, що кільцева швидкість потоку пилогазової суміші на кожній ступені млина у 1,77 рази менше швидкості бил.

In article the method of calculation of speed powder-gas mix in a working zone of a shock - reflective mill is offered on the basis of the capacity which spent by a mill on overcoming of resistance beaters to a stream powder-gas mix. Is established, that district speed of a stream powder-gas mix on everyone stage mill in 1,77 times less then speed beaters.
Keywords: скорость движения материалов; крупный помол; пылегазовая смесь; скорость бил; средний помол